2022
DOI: 10.3390/ijms23020800
|View full text |Cite
|
Sign up to set email alerts
|

The Epithelial–Mesenchymal Transition at the Crossroads between Metabolism and Tumor Progression

Abstract: The transition between epithelial and mesenchymal phenotype is emerging as a key determinant of tumor cell invasion and metastasis. It is a plastic process in which epithelial cells first acquire the ability to invade the extracellular matrix and migrate into the bloodstream via transdifferentiation into mesenchymal cells, a phenomenon known as epithelial–mesenchymal transition (EMT), and then reacquire the epithelial phenotype, the reverse process called mesenchymal–epithelial transition (MET), to colonize a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 215 publications
1
53
0
Order By: Relevance
“…In recent works, we have demonstrated for the first time that alterations in glycosylation in tumor cells chronically exposed to chemotherapeutic agents, are able to connect both MDR phenotype and EMT process, since in addition to presenting changes in the expression and/or activity of efflux pumps belonging to the ABC superfamily (ABCB1, ABCC1 and ABCG2) [55,56], the chemoresistant human cancer cell lines also showed increased cell motility, as well as altered expression of epithelial-mesenchymal markers, when compared with their normal counterparts [34,35]. These findings confirm the idea that both accretion of MDR phenotype and the activation of EMT process, which have been considered indispensable for invasion and metastasis [57][58][59], are deeply linked with unusual glycan structures expressed by transformed cells. In our previous study we also observed that the chronic exposure to non-lethal concentrations of cisplatin induced the expression of an isoform of fibronectin (FN), so called oncofetal FN (onf-FN) [35], which may be found in transformed cells, and embryonic samples, but is absent in normal tissues [6].…”
supporting
confidence: 76%
“…In recent works, we have demonstrated for the first time that alterations in glycosylation in tumor cells chronically exposed to chemotherapeutic agents, are able to connect both MDR phenotype and EMT process, since in addition to presenting changes in the expression and/or activity of efflux pumps belonging to the ABC superfamily (ABCB1, ABCC1 and ABCG2) [55,56], the chemoresistant human cancer cell lines also showed increased cell motility, as well as altered expression of epithelial-mesenchymal markers, when compared with their normal counterparts [34,35]. These findings confirm the idea that both accretion of MDR phenotype and the activation of EMT process, which have been considered indispensable for invasion and metastasis [57][58][59], are deeply linked with unusual glycan structures expressed by transformed cells. In our previous study we also observed that the chronic exposure to non-lethal concentrations of cisplatin induced the expression of an isoform of fibronectin (FN), so called oncofetal FN (onf-FN) [35], which may be found in transformed cells, and embryonic samples, but is absent in normal tissues [6].…”
supporting
confidence: 76%
“…Our results also showed that HELLS activates the EMT pathway in cancers and that HELLS expression positively correlates with EMT in AML. EMT enhances the migratory and invasive potential of malignant tumor cells, which may trigger anti-apoptosis and degradation of the extracellular matrix ( 57 ). Previous studies ( 58 , 59 ) found that HELLS can mediate EMT in nasopharyngeal carcinoma cells by altering intermediates of tricarboxylic acid metabolism in cancer cells, promoting their migration, invasion, and progression.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that CXCR4 is expressed only in ESCC tissues but not in the normal esophageal epithelium ( 102 ). Expression of CXCL12 or CXCR4 in ESCC patients is significantly related to ESCC invasion, lymph node metastasis, and poor survival ( 103 , 104 ). It has been shown that ESCC cells could secrete large amounts of CXCL12 via an autocrine way and increase their receptor CXCR4 expression compared with normal cells ( 105 ).…”
Section: The Role Of Cellular Communication In Esophageal Squamous Ce...mentioning
confidence: 99%